Pengembangan Media Pembelajaran Biologi Berbasis Video Animasi Stop Motion sebagai Sumber Belajar Siswa SMA/MA - Putri, Ananda; Nur, Fadilla Annisa; Sari, Nabila Syahna Permata; Nurliana, Maulidya; Rahayu, Reni; Daulay, Rabiah Afifah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this development and research is to ensure whether the stop motion video learning media is effective in teaching Biology material on the human circulatory system. Experts in the field of media and materials have evaluated this idea. The development model used in this research is the ADDIE model. The subjects of this study are 11th grade high school students. The instrument used is a student response questionnaire. The data analysis results show that the expert lecturer's validation of the feasibility of stop motion videos scored 4.0 with a good category, and the reliability test shows an agreement percentage of 85.3% (reliable). Other reliability test results show an agreement percentage of 80.1% (reliable), with a stop motion video feasibility validation score of 3.9 and a good category. From these results, it can be concluded that the use of stop motion videos in teaching the human circulatory system material is very possible and can be one alternative method for learning Biology.